PRODUCTION OF GOAT POX VIRUS VACCINE FROM A LIVE ATTENUATED GOAT POX VIRUS STRAIN - F. Abbas; F. A. Khan; A. Hussain; F. Ahmed; M. Ahmed; S. Ahmed; M. Z. Ahmed; M. A. Attique; A. Wadood; M. K. Taj. (Journal of Animal and Plant Sciences, 2010)
Kid kidney cells form less than 2 months of age were grown, 80% confluent monolayers were obtained after 10-12 days.   Live attenuated goat pox virus vaccine (Gorgan 55, Iranian) was used to infect the confluent monolayers.   Eighty percent cytopethic effect (CPE) was obtained on day 5 of virus inoculation.  TCID50 calculated for the pool virus was 10 5.5/ ml.  Vaccine was found free from any bacterial and mycoplasma contamination. All mice and guinea pigs were found healthy after 21days post vaccinal administration.  Vaccinated goats challenged after 14 days with 1 ml of virulent goat pox virus (TCID50 104.5/ml) did not show any unwanted reaction while controls challenged with 1 ml of virulent goat pox virus (TCID50 10 3.5/ml)  showed pox lesions and rise in body temperature. The main objective of this study was to produce and study the efficacy of this vaccine.
Keywords: attenuated; goat pox virus; confluent; monolayer; virulent; challenge